Canton and Mediterranean mutations among Chinese and Malay newborns with G6PD abnormalities in UKMMC / Nurulfatihah Samuri - Samuri, Nurulfatihah (2015)
Glucose-6-Phosphate Dehydrogenase (G6PD) is an enzyme that helps in the protection of red blood cells against oxidative stress. G6PD deficiency, which is an X-linked genetic disorder, is the commonest enzyme defect in human. It will cause erythrocytes to breakdown prematurely and lead to a hemolytic condition. There are several classes of genetic variants for G6PD deficiency. The variants are classified according to severity of deficiency. Determination of the severity will help in monitoring and prevention from occurrence of complication such as kernicterus which can lead to death. In order to identify the type of variant, molecular technique is the method of choice. However, prior to the implementation of any molecular method, data on the percentage of common G6PD mutations for a specific population within a geographic area is required. Therefore, the study was conducted to detect the presence of Canton and Mediterranean mutations among Chinese and Malay newborns with abnormal G6PD in UKM Medical Centre. Cord blood samples from newborns with abnormal G6PD (80 Malay and 23 Chinese) were selected based on their FST and G6PD enzyme level assay results. The detection of mutations was performed using 7500 Fast Real-Time Polymerase Chain Reaction. The results showed that the Mediterranean mutation was present in twelve of the Malay newborns while the Canton mutation was detected in six of the Chinese newborns. Out of the twelve Malay newborns, ten were detected as homozygote, while two newborns were detected as heterozygote. Meanwhile, out of six Chinese newborns, three were heterozygote and three were homozygote. As for the remaining sixty-eight Malays newborns and seventeen Chinese newborns, they were detected as wild-type. However, beside these two mutations, there are other common G6PD mutations. Thus, there is a high possibility that the undetected newborns may have one of the other common mutations which were not screened in the present study. In conclusion, the Canton and Mediterranean mutations were detected among Chinese and Malay newborns with abnormal G6PD status in UKMMC with prevalence of 26.09% and 15% respectively.